Healthcare resource utilization and costs associated with postpartum depression among commercially insured households. (2nd October 2020) - Epperson, C. Neill; Huang, Ming-Yi; Cook, Keziah; Gupta, Deepshekhar; Chawla, Anita; Greenberg, Paul E.; Eldar-Lissai, Adi
Abstract: Objective: To quantify the economic burden of postpartum depression (PPD) that accrues to commercially insured households in the year following childbirth. Methods: Administrative claims data from OptumHealth Care Solutions (2009–2016) were used to identify households that included women identified with PPD per the algorithm and propensity score–matched comparison households of women who were not identified with PPD or a history of depression after childbirth. Study outcomes included direct total all-cause medical and pharmaceutical costs during the first year following childbirth and number of outpatient visits at the household level stratified by household member. Results: Households affected by PPD as identified by the algorithm ( N  = 7769) incurred 22% higher mean total all-cause medical and pharmaceutical spending than unaffected matched controls ( N  = 41, 308) during the first year following childbirth ($36, 049 versus $29, 448, p  < 0.01) and an average of 16 more outpatient visits than unaffected households ( p  < .01). Costs accrued by mothers comprised the largest share (>50%) of total all-cause spending. Mothers identified with PPD had significantly higher annual mean direct total all-cause medical and pharmaceutical spending than their matched controls without PPD ($19, 611 versus $15, 410, p  < .01), driven primarily by an average of 11 more outpatient visits than unaffected mothers ( p  < .01). Conclusions: Households affected by PPD as identified by the algorithm incurred higher mean total all-cause medical and pharmaceutical spending during the first year following childbirth than did their matched controls identified without PPD, but not all costs were attributable to maternal treatment for PPD. These findings contribute to a better understanding of the potential economic burden associated with PPD and demonstrated costs may extend beyond the mother to members of the household.